2004
DOI: 10.1074/jbc.m312716200
|View full text |Cite
|
Sign up to set email alerts
|

A Glutamate Is the Essential Proton Transfer Gate during the Catalytic Cycle of the [NiFe] Hydrogenase

Abstract: Kinetic, EPR, and Fourier transform infrared spectroscopic analysis of Desulfovibrio fructosovorans [NiFe]hydrogenase mutants targeted to Glu-25 indicated that this amino acid participates in proton transfer between the active site and the protein surface during the catalytic cycle. Replacement of that glutamic residue by a glutamine did not modify the spectroscopic properties of the enzyme but cancelled the catalytic activity except the para-H 2 /ortho-H 2 conversion. This mutation impaired the fast proton tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
187
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 140 publications
(197 citation statements)
references
References 48 publications
9
187
0
1
Order By: Relevance
“…In the oxidized as-prepared state, both mutants exhibit spectra similar to those reported for the WT enzyme (22). The oxidized active site normally gives a superposition of signals called Ni-A (g ϭ 2.31, 2.23, 2.01) and Ni-B (g ϭ 2.34, 2.16, 2.01).…”
Section: Resultsmentioning
confidence: 48%
See 2 more Smart Citations
“…In the oxidized as-prepared state, both mutants exhibit spectra similar to those reported for the WT enzyme (22). The oxidized active site normally gives a superposition of signals called Ni-A (g ϭ 2.31, 2.23, 2.01) and Ni-B (g ϭ 2.34, 2.16, 2.01).…”
Section: Resultsmentioning
confidence: 48%
“…The assays of H2 oxidation were carried out after the enzymes were activated (22). The isotope-exchange assay is described in ref.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous work, it has been observed that proton exchange within proteins can be facilitated via negatively charged side chains and water molecules (25)(26)(27). Understand-ing this key mechanism in [FeFe]-hydrogenases is critical for targeted protein engineering, as perturbing proton transfer can cause unintended deleterious effects on the catalytic rate (28). To date, detailed experiments investigating proton transport within [FeFe]-hydrogenases have not been reported.…”
mentioning
confidence: 99%
“…It has been proposed that the enzyme interconverts between NiSI and NiR when catalyzing HDE (20,21). A combination of these three assays has been used to investigate PT in hydrogenase (22,23); for example, if a certain variant is affected in both H 2 production/oxidation and H/D exchange, but catalyzes the conversion between para and ortho H 2 , then it is likely that the mutated residue is involved in PT. This approach was used to show that Glu-25 L in the large subunit of the enzyme from Df and Glu-13 L in the sensor enzyme from Ralstonia eutropha are essential for PT (22,23).…”
mentioning
confidence: 99%